Analysis and modelling of iBeacon wireless signal propagation in multiple environments. (30th November 2021) - Zeng, Luchuan; He, Zhifei; Tan, Zherui; Geng, Renliang; Liu, Menghua; Xia, Linglin; Lin, Deyu
IBeacon positioning accuracy is usually influenced by its signal quality in practical environments. The purpose of this study is to provide users with a reasonable iBeacon networking deployment scheme to improve the accuracy of positioning. We explore the characteristics of iBeacon signal propagation and existing propagation path loss in common environments (corridor, playground, classroom). Firstly, the changes of received signal strength indicate (RSSI) value of iBeacon wireless signal under three environments are collected, and then the signal samples are filtered numerically. Secondly, a simplified single-slope and a double-slope propagation models are used to simulate iBeacon signal propagation. Finally, the models are used to carry out regression analysis on the sample data under different scenarios, and the best applicable scenario of the two models is determined according to the results. In conclusions, based on the simulation results of the propagation model, this study provides some suggestions for users to deploy iBeacons indoors or outdoors.